1990
DOI: 10.1111/j.1476-5381.1990.tb15848.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of cyclic GMP in adenosine‐induced, age‐dependent vasodilatation

Abstract: 1 Adenosine-induced dilatation of rat aorta was present in aorta taken from 4 week-old rats, attenuated with increase in age of rats to 8 weeks, and was virtually absent in the aorta from 12 week-old rats. 2 Removal of the endothelium by mechanical rubbing attenuated adenosine-induced dilatation. 3 Haemoglobin and methylene blue partly reversed the adenosine-induced endothelium-dependent dilatation. 4 The order of potency of adenosine derivatives was 5'-(N-ethylcarboxamido)indicating that adenosine receptors m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 38 publications
(45 reference statements)
5
21
0
Order By: Relevance
“…A decrease in the production/ accumulation of cyclic GMP which is known to be a second messenger in vascular relaxation (Rapoport & Murad, 1983), is undoubtedly the major cause of age-associated reduction of PAF-induced relaxation. Essentially similar age-dependent changes in relaxant responses and cyclic GMP production in rat thoracic aorta have been documented with histamine (Moritoki et al, 1986;, adenosine (Moritoki et al, 1990) and ATP (Ueda & Moritoki, 1991).…”
Section: Discussionsupporting
confidence: 52%
“…A decrease in the production/ accumulation of cyclic GMP which is known to be a second messenger in vascular relaxation (Rapoport & Murad, 1983), is undoubtedly the major cause of age-associated reduction of PAF-induced relaxation. Essentially similar age-dependent changes in relaxant responses and cyclic GMP production in rat thoracic aorta have been documented with histamine (Moritoki et al, 1986;, adenosine (Moritoki et al, 1990) and ATP (Ueda & Moritoki, 1991).…”
Section: Discussionsupporting
confidence: 52%
“…In guinea pig aorta, both A 1 and A 2 receptor subtypes were identified (Stoggall and Shaw, 1990), with some evidence for the expression of A 2B receptors (Martin, 1992). A 2 receptors are involved in endothelium-dependent relaxation of rat thoracic aorta (Moritoki et al, 1990;Rose'Meyer and Hope, 1990). Later articles have identified adenosine A 2A receptors as the mediators of rat aortic endothelium-dependent vasodilation (Lewis et al, 1994;Ray and Marshall, 2006;Nayeem et al, 2008), although A 2B receptors have also been implicated (Ansari et al, 2007a).…”
Section: +mentioning
confidence: 99%
“…In order to avoid potential variation due to the difference in the individual vascular reactivity, the vascular preparations have been obtained from the same animal. Since STZ-induced diabetes is associated with a dramatic body weight loss and because adenosine-induced vasodilation is gradually diminished with advancing age in the rat (Moritoki et al 1990;Headrick 1996), two groups of control rats have also been considered: a group of weight and agematched rats, respectively. Additionally, despite the fact that the vascular effect of adenosine has classically been ascribed to an endothelium-independent process (Fredholm et al 1994), some workers have reported that its vascular relaxant effect was, at least in part, dependent on the presence of a functional vascular endothelium (Moritoki et al 1990;Rose'Meyer and Hope 1990;Abebe et al 1994;Lewis et al 1994).…”
Section: Introductionmentioning
confidence: 99%